RESOURCE MANAGEMENT AND FINANCIAL SUCCESS: AN EMPIRICAL EXAMINATION OF WORKING CAPITAL IN NIGERIA’S CONSUMER GOODS SECTOR - Ojo, Mary Olufunke; Fasina, Samuel Oluwadare (Research Journal of Economics and Sustainable Development, 2024)
This study analyzes the impact of working capital management on the financial performance of quoted consumer goods sector in Nigeria over a period of 10 years, from 2011 to 2020. Data from nine companies were utilized through the panel regression method to determine the correlation between various working capital components and financial performance. The results of the analysis revealed that working capital management has no significant effect on the financial performance of the selected firms during the study period. The study recommends that organizations should pay more attention to working capital management to ensure it is appropriately balanced between profitability and liquidity. Effective management of inventory turnover, trade receivables collection period, trade payables payment period, and cash conversion cycle are essential aspects of working capital management. The study emphasizes the importance of striking a balance between liquidity and profitability in working capital management to ensure long-term business success.